Interrogating the doctrine of fair hearing in the Nigerian constitution and the a-gbo-ejo-enikan-da-agba-osika in the Yoruba socio-cultural milieu (2024)
The right to a fair hearing as contained in the 1999 Constitution of the Federal Republic oi Nigeria, as amended, is as old as mankind. The doctrine of fair hearing which could be said to have existed with the first man in the garden of Eden, featured where God did not condemn either of the parties, but sought to hear from them before making a decision. The doctrine, simply put, means that in any matter for adjudication, each party should be given ample opportunity to present their case. Existing studies on fair hearing which has in it, the twin pillars of natural justice of Audi alteram partem (Hear the other side) and Nemo judex in causa sua (One cannot be a judge in his own case) and its implication on Nigeria's legal System and peacemaking process have focused on the legal, administrative, sociological and political perspectives. While some are of the view that the doctrine is not relevant in the Contemporary time, due to the intricacies involved in it, others believe that the system is as relevant as ever. For them, it is the only way the masses can have a sense of hope in a country where justice is believed to be delayed and denied with impunity. However, the focus of this paper is to explore the doctrine of fair hearing in the Constitution of the Federal Republic of Nigeria vis a vis the Yoruba adjudicatory process of settling disputes (A gbo Ejo Enikan da, agba osika) which has over the years been applied for the sustenance of peace and order in Yoruba society. Methodologically, this paper relied on secondary sources for data collection. Recommendations are made for the incorporation of the two adjudicatory processes where necessary to ensure a just and peaceful society.